Revitalization as a Regulatory Strategy in Rawa Pening Lake Management (Case Study in Dusun Sido Makmur, Sumber Rejo, Semarang Regency) - Siti Suci Wulandari (Endogami: Jurnal Ilmiah Kajian Antropologi, 2022)
Topographic maps and satellite imagery of the estuary of Lake Rawa Pening from 1918 to the present show that Lake Rawa Pening has experienced expansive silting due to sedimentation. To overcome this problem, the government wanted to improve the situation by revitalizing Rawa Pening. However, that good intention did not go well. Thus, this study seeks to examine the effectiveness of the govermentality in the context of community resistance around the Rawa Pening Lake area to deal with the revitalization program. This study used an ethnographic approach supported by a map of Lake Rawa Pening. The collection technique was through participant observation, in-depth interviews, and documentation. The findings show that the govermentality does not always run according to the technicalization of the planned problem. This is due to the revitalization with the exclusion of community-owned land in determining the boundary line of the Rawa Pening Lake, which is supported by the Decree of the Minister of PUPR No. 365/KPTS/M/2020. This situation gave rise to resistance from the community: the submission of a letter of reinvention of the policy, the establishment of the Wasdalin institution, mujahadah, and the distribution of ownership certificates on Right of Ownership (SHM) land and houses. Furthermore, there is a neglect of social navigation abilities. The resistances carried out by the community are tidal farming, looking for water hyacinth, water hyacinth crafts, selling fish, fishing and aquaculture. Thus the regulation in its implementation does not always run well but often faces various obstacles and resistance from the community following the power relation and govermentality practices.